Insights From the Science of Learning Can Inform Evidence-Based Implementation of Peer Instruction - Schell, Julie A.; Butler, Andrew C. (Frontiers in Education, 2018)
Peer Instruction is a popular pedagogical method developed by Eric Mazur in the 1990s. Educational researchers, administrators, and teachers laud Peer Instruction as an easy-to-use teaching method that fosters active learning in K-12, undergraduate, and graduate classrooms across the globe. Research over the past 25 years has demonstrated that courses that incorporate Peer Instruction produce greater student achievement compared to traditional lecture-based courses. These empirical studies show that Peer Instruction produces a host of valuable learning outcomes, such as better conceptual understanding, more effective problem-solving skills, increased student engagement, and greater student retention in science majors. The diffusion of Peer Instruction has been widespread because of its effectiveness, simplicity, and the flexibility. However, a consequence of its flexibility is wide variability in implementation. Teachers frequently innovate or personalize the method by making modifications, and often such changes are made without research-supported guidelines or awareness of the potential impact on student learning. The present article presents a framework for guiding modifications to Peer Instruction based on theory and findings from the science of learning. We analyze the Peer Instruction method with the goal of helping teachers understand why it is effective. We also consider six common modifications made by educators through the lens of retrieval-based learning and offer specific guidelines to aid in effective implementation. Peer Instruction is a powerful way for educators to encourage active learning, but effective implementation requires making informed decisions about modifications. Educators must be free to innovate and adapt teaching methods to their classroom.